Salivary and serum cortisol levels during recovery from intense exercise and prolonged, moderate exercise - Powell, Jeffrey; DiLeo, Travis; Roberge, Raymond; Coca, Aitor; Kim, Jung-Hyun (Biology of Sport, 2015)
The aim of this study was to compare serum (SERc) and salivary cortisol (SALc) responses during recovery from two different exhaustive exercises to determine peak cortisol sampling time and the agreement between SERc and SALc levels. Twelve healthy men underwent a maximal treadmill graded exercise to exhaustion (MEx) and a prolonged, submaximal cycle exercise in the heat for 90 min (PEx) while SERc and SALc samples were taken in parallel at baseline, end of exercise, and 15 min intervals over one hour of recovery. MEx and PEx significantly increased SERc and SALc levels (p<0.01) while absolute SERc levels were approximately 7-10 folds higher than SALc. SERc and SALc showed highly positive correlation (R=0.667-0.910, p<0.05) at most sampling times and only a few individual values were out of 95% limit of agreement when analyzed by Bland-Altman plots. However, peak SERc levels (MEx: 784.0±147, PEx: 705.5±212.0 nmol · L-1) occurred at 15 min of recovery, whereas peak SALc levels (MEx: 102.7±46.4, PEx: 95.7±40.9 nmol · L-1) were achieved at the end of exercise in MEx and PEx. The recovery trend of SERc and SALc also differed following MEx and PEx. Activity of 11β-hydroxysteroid dehydrogenase type 2 enzymes may be suppressed following MEx compared to PEx. In conclusion, sampling for peak SERc and SALc levels should take into account their evolution and clearance characteristics as well as type of exercise performed, whereas SALc appeared to be a more sensitive marker than SERc for the measurement of cortisol responses during exercise recovery.